Pitfalls in prenatal diagnosis of beta thalassaemia. Issue 5 (October 1986) - Rosatelli, C; Maccioni, L; Scalas, M T; Cao, A
Abstract : In this paper, we report a pregnancy at risk for beta thalassaemia in which the fetal red blood cell volume was reduced while that of the mother was relatively great, so that the presence of a fetal red blood cell population in a mixed maternal-fetal sample was difficult to recognise. The molecular basis for these haematological phenotypes was clarified by follow up examination and alpha globin gene mapping. These indicated that the fetus was heterozygous for beta thalassaemia and had deletion of three alpha globin structural genes, while the mother, heterozygous for beta thalassaemia, also had deletion of two alpha globin structural genes. When the coinheritance of alpha thalassaemia is suspected, it is necessary to examine carefully the red blood cell distribution of a placental sample, so that the presence of a population of fetal red blood cells is not missed.